2011
DOI: 10.1159/000323815
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Lipoprotein Parameters and C-Reactive Protein in Patients with Age-Related Macular Degeneration

Abstract: Background: Age-related macular degeneration (AMD) is the most common cause of visual impairment in individuals over 50 years of age, with the prevalence of 0.05% before the age of 50 rising to 30% after 74 years of age. An elevated concentration of plasma lipoproteins is considered to be one of the risk factors of AMD development. The aim of our study was to analyze the concentration of serum lipoproteins – total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), non-LDL cholesterol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 56 publications
1
17
1
Order By: Relevance
“…With the exception of the study conducted by Colak et al [9], all of these studies showed a protective tendency. The pooling of these studies in the meta-analysis yielded an RR of the LDL level of 0.93 (95% CI, 0.88 to 0.99; I 2 = 0; p = 0.83; Figure 3) for an increment of 1 mmol/L, without heterogeneity.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…With the exception of the study conducted by Colak et al [9], all of these studies showed a protective tendency. The pooling of these studies in the meta-analysis yielded an RR of the LDL level of 0.93 (95% CI, 0.88 to 0.99; I 2 = 0; p = 0.83; Figure 3) for an increment of 1 mmol/L, without heterogeneity.…”
Section: Resultsmentioning
confidence: 93%
“…After reviewing the full-text articles, 21 articles (19 studies) were included in this meta-analysis (Figure 1) [8,9,10,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found higher levels of plasma CRP levels in AMD patients compared to healthy controls (Colak et al, 2011; Hong et al, 2011; Robman et al, 2010; Seddon et al, 2004; Yasuma et al, 2010). Seddon et al found that CRP was significantly associated with the presence of both intermediate and advanced stages of AMD (OR=1.65, P=0.02) (Seddon et al, 2004).…”
Section: Biomarkers Of Disease and Progressionmentioning
confidence: 99%
“…We are currently applying the evidence base presented in Table 2 and Figure 1 to guide investigations designed to identify core elements of a "molecular phenotype" (a pattern gene regulation/expression and DNA variation) representing individual capacity to use transporters, receptors, enzymes, and hormones targeting or affected by MXs in ways that may reduce risk of AMD incidence or progression. Although we have not yet identified any single sequence variant explaining a proportion of variance in AMD risk comparable to those of the complement pathway genes, there is now informative work examining putative AMD-associated single-nucleotide polymorphisms present in genes encoding proteins involved in MX transport (121,131,137,146,(148)(149)(150)(151)(152)(153)(154)(156)(157)(158)(159)(160)(161), binding/capture (141,162,163), cleavage (158,160), and diseases associated with lower MX status (177)(178)(179)(180)(181)(182)(183)(184). Projects examining the associations of MX-related genes with retinal pathophysiology in in vivo models have supported inferences on AMD relations with variants in MX transport genes (128,130,136,143).…”
Section: The Promise Of Molecular Genetics For Examining the Effect Omentioning
confidence: 99%